The Influence Of Entrepreneurial Competence And Principal Supervision On Teacher Performance at SD - Warda, Warda; Hastati, Sri; Nurjannah, Sitti (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
During initial observations in June 2024 at UPT SPF SD Inpres Kera-kera, teacher performance was well identified from planning, implementation to learning evaluation. However, there are still gaps that make implementation less than optimal, such as the lack of innovation and new ideas for educational development. Ineffective principal supervision and poor communication also hamper teacher performance. The results of the study indicate that: 1) the influence of entrepreneurial competence of the principal on teacher performance with both aspects playing an important role in improving education in schools. 2) the influence of principal supervision on teacher performance is interrelated, this can be seen from the principal's supervision which includes planning academic supervision programs, implementing academic supervision, and following up on the results of academic supervision effectively playing a direct role in implementing teacher performance at school. 3). Knowing the influence between entrepreneurial competence and principal supervision has a positive and significant influence on teacher performance at UPT SPF SD Inpres Kera-Kera, with the results of the multiple linear regression hypothesis test obtained with a significance value of 0.003